Measurement of Growth, Photosynthesis and Transpiration Rates of a Malaysian Local Rice Cultivar (Mr 219) for Assessing Ambient Ozone Stress - Shahadan, Nurul Azzura (2005)
Ambient air pollution has been shown to reduce the yield of several major crops species. Research and field observations have suggested that O3 may responsible for up to 90% of tlie crop loss induces by air pollutants. One approach that has been used to estimate effects of ozone 011 yield is by determination critical Oj levels cumulated exposure over tlie threshold of 49 ppb ( ~ 0 7 4 0 ) . Thc AOT40 is calculated as tlie sum of'tlie differences between the hollrly ozone concentrations in ppb and 40 ppb for cacli hour \\lien the concentration exceeds 40 ppb. 'fliis study is aimed to in~estignteth e responses of Malaysian local rice ci~ltivar( MR 2 19) to ci~rrent ambient ozone (0;) in Muda Agriculti~ral Development Autlinrity (MAIIA). Open top clia~nberst hat ventilated with ambient air and charcoal-filtered air was used to assess the impact of air pollution on the physiology and growth o!' rice. I'lie rice crop was grown according to the local crop management practice \\ itli I . C S ~ C Cto~ the rate of fertilizer and pesticides application and water supply. The result sho\i,ed the plant height in the non-filtered chamber decreased by 2.8% at \cgetative stage, 12.1% at reproductive stage and 6.1% at ripel:ing stage as compared to the crop gro\\n in the filtered chamber. Average number of tillers per point in the filtered chamber \\as 14. nith a maximum of 29. \\hereas for nonfiltered chamber it was 1 I \\it11 a ma\in~uni of24. I n general, the relative grouth rate (RGRd,,) for all plant parts were Iligher in stage I than in stage I1 and 111. The stariqtical analysis of RGR*,, for all plant parts werc not significant different at 95% confident level. l he study also indicated that the pollutant affected the physiolog! no st during the vegetative stage. Photos! nthesis rate (P,) was observed to be significant different at the 95% confident level bet\\een filtered and non-filtered plant at \egetative stage. Photosynthetic capacit) (P,,,.,,) in filtered plant was 18.8 p o l CO: ~n-' s-I, and 12 ynol C02 ni-2 s-' in non-tiltercd plmr during the vegetative stage. At reproductive \tage the difference in 1d1010~!111h~\i!r, ate between filtered and nnn-filtered plant \ia s not significant (9j00 conticlcn~It .\ el). Photosynthetic capacitj (P,.,,) , in the nonfiltered plant was 13.9 p o l C.0: 111 s-I. and 13.5 pt11ol CO: m-' s" for the filtered plant. 'l'he transpiration rate (/<I dit'!i.rct:;i.> between the plants in the filtered and nonfiltered chamber \\,as signitica:?: it)!% confident level) during the \.egetative stage but not during reproducti\c 3ta;i'. I lie differences in stomata conduct::nce between tlic liltered and non-1iltcrc.d plarith during thc vegetative and rcproductivc stages wcrc not significant ( ~ 5 "co~n)ri cicrit level). PEFiPUSTM(AAN SULTAN ABDUL SAMAD UNIVElHTI PUTXA MALAYSIA At the final harvest, the differences in yield between the filtered and non-filtered chambers at 95% confidence level was significant. The average of total weight of grain in the filtered chamber was 120.7g per plant and 90.978 per plant in nonliltrred chamber. The mean 100 yields grain weight for filtered and non-filtered chambers were 2.71g and 2.578, respectively. However, the difference between 100 filled grain weight for the two chambers was not significant (95% confidence level).